Effect of foliar spraying with Zn and different levels of phosphatic fertilizer on growth and yield of sunflower plants grown under saline condition - Thalooth, A. T.; Badr, N.M.; Mohamed, M.H. (2005)
A POT experiment was carried out during the summer season of 2001 in the green house of National Research Centre, Dokki, Giza Egypt. This work aimed to study the interaction effect of different rates of phosphorus (fetilization (32, 48 and 64 P20S kg/fad) and foliar spraying with zinc (without spray, spray once after 30 days from sowing and twice after 30 and 45 days from sowing) on growth and yield of sunflower plants grown under salinity conditions.
Includes references.
Summary in Arabic.
1
Keywords: Sunflowers -- Fertilizers; Sunflowers -- Yields; Foliar feeding; Sunflowers -- Growth; Plants -- Effect of salt on